EXPLANATION
Considering the table below and the equation -10x -y = -20, we can fill it as follows:
-10x -y = -20
Adding +10x to both sides:
-y = -20 + 10x
Dividing both sides by -1:
y = 20 - 10x
x y= 20 - 10x (x,y)
-- --------------------------- -----------
0 y= 20 - 10(0)= 20 (0,20)
1 y= 20 - 10(1) = 20 -10= 10 (1,10)
0 = 20 - 10(x) --> Adding +10x to both sides:
10x = 20 --> Dividing both sides by 10:
2 x= 20/10 = 2 --> (2,0)
So, rearranging the table:
x y (x,y)
-- --------------------------- -----------
0 20 (0,20)
1 10 (1,10)
2 0 (2,0)